Acute Hemolysis with Renal Failure due to Clostridium Bacteremia in a Patient with AML - R. M. Medrano-Juarez; D. Sotello; M. A. Orellana-Barrios; L. D’Cuhna; J. D. Payne; K. Nugent (Case Reports in Infectious Diseases, 2016)
We present a case of acute hemolytic anemia, renal failure, and Clostridium perfringens bacteremia in a patient with acute myelogenous leukemia. The high fatality of C. perfringens bacteremia requires that clinicians recognize and rapidly treat patients at risk for this infection. Although other hemolytic processes are in the differential diagnosis of these events, the presence of high fever, chills, and rapidly positive blood cultures may help narrow the diagnosis. Most cases of C. perfringens bacteremia have a concomitant coinfection, which makes broad spectrum empiric therapy essential. There is a high mortality rate of C. perfringens infections associated with leukemia.